A successful treatment case of refractory hemorrhagic ulcer with eosinophilic gastritis by endoscopic hand suturing. Issue 1 (9th January 2023) - Nakagome, Shun; Koizumi, Eriko; Goto, Osamu; Kitamura, Michika; Kawami, Noriyuki; Higuchi, Kazutoshi; Onda, Takeshi; Omori, Jun; Akimoto, Naohiko; Iwakiri, Katsuhiko
Abstract: A 78‐year‐old man was admitted to our hospital with a tarry stool. Esophagogastroduodenoscopy identified tiny oozing on the greater curvature at the antrum. Despite repeated endoscopic hemostasis by coagulation and clipping, rebleeding occurred. On the third rebleeding, we performed endoscopic hand suturing to completely close the ulcer surface. Biopsy showing massive infiltration of eosinophils at the ulcer edge indicated eosinophilic gastritis. After the endoscopic closure by endoscopic hand suturing, the patient had no symptoms of bleeding thereafter and was discharged 19 days after the procedure by taking oral prednisolone. The patient remained well and was continuously treated with a small dose of steroids in outpatient. This is the first case report of the successful application of endoscopic hand suturing to a refractory hemorrhagic ulcer. Further accumulation of clinical experiences is desired to confirm the usefulness of this technique for the prevention of refractory ulcer bleeding.